Caracterización de fracciones mayoritarias del plasma seminal humano. Estudio comparative entre individuos normospérmicos, azoospérmicos, necrozoospérmicos, oligozoospérmicos y vasectomizados - Tortorella, Helen; Konrath, Renato O.; Brandelli, Adriano; Furtado, João L. F.; Mazzini, María N. (My University, 1996)
Normospermic and pathological human seminal plasma (PSH) was analysed by affinity chromatography in Concanavalin-A Sepharose. Two main fractions were obtained, F1 and F2, in variable proportions and with different glycan content according with the type of pathology. Characterization of the oligosaccharide chains of F1 and F2 showed that galactose is always the main component together with fucose and variable amounts of mannose, N-acetylglucosamine and N-acetylgalactosamine. These fractions showed differences in the primary structure of glycoprotein glycans (N- and O-glycosidic-linked), according to the pathology. All the oligosaccharide chains in F1 correspond to mucin type glycoproteins (O-glycosidic type), whereas in F2 the molar ratio O-/N- is 5.3/1. F1 from azoospermic and oligozoospermic are nearly all of the O-glycosid type while in vasectomised the oligosaccharide chains differ from the other ones by a molar ratio O-/N- of 1.7/1. F2 present both O- and N- oligosaccharide chains in different amounts, with the only exception of vasectomised which belongs to O-glycosid type. The results obtained suggest that the composition of major PSH fractions from donors with different pathologies is characterized by marked structural differences on the glycan and the protein moiety.
Keywords: Affinity chromatography; Carbohydrate; Glycoprotein; Lectin; Semen